2013
DOI: 10.1159/000362785
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Methicillin-Resistant <b><i>Staphylococcus aureus</i></b>: Effect of Different Criteria for Elimination of Duplicates

Abstract: Background: The purpose of this study is to compare the effect of different systems for eliminating duplicates in order to optimize the calculation of the prevalence of methicillin-resistant Staphylococcus aureus (MRSA) infection. Methods: We compare the Clinical and Laboratory Standards Institute (CLSI) criterion, time criteria and the criterion recommended by the European Antimicrobial Surveillance System (EARSS). Results: Multiple isolates of MRSA are frequently recovered from successive cultures from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
1
Order By: Relevance
“…In previous studies, resistance rates were often similar for different specimen types or showed merely unpredictable deviations [ 7 , 10 , 23 , 29 ]. However, one study found mainly higher resistance rates of blood culture isolates for several examined species/antibiotic combinations [ 32 ] which is in contrast to our data, whereas another study also found lower resistance rates in Staphylococcus aureus isolates from normally sterile body sites [ 13 ].…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In previous studies, resistance rates were often similar for different specimen types or showed merely unpredictable deviations [ 7 , 10 , 23 , 29 ]. However, one study found mainly higher resistance rates of blood culture isolates for several examined species/antibiotic combinations [ 32 ] which is in contrast to our data, whereas another study also found lower resistance rates in Staphylococcus aureus isolates from normally sterile body sites [ 13 ].…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, comparability of different studies is limited and it is not possible to confidently predict the effect of a duplicate isolate removal. However, previous studies mainly showed an decrease in resistance rates with the exclusion of duplicate isolates similar to our findings, albeit analyses were often limited to a single species or used fewer methods for duplicate isolate removal: Regarding the MRSA percentage, decreases by up to 35 percentage points were found in different studies, and the effect depended on duplicate isolate removal strategy, patient population, observation period, study site and sample type [ 7 , 9 , 13 15 ]. Regarding other species/antibiotic combinations, decreases in resistance rates by up to 5 percentage points were found for urinary tract isolates [ 16 ], up to 12 and 18 percentage points for Escherichia coli and Pseudomonas aeruginosa isolates [ 10 ] and up to 19 and 11 percentage points for Klebsiella pneumoniae and Acinetobacter baumannii isolates [ 15 ].…”
Section: Resultssupporting
confidence: 85%
“…Noguera et al 29 showed that the CLSI strategy has serious limitations, since it does not identify the presence of many isolates that may be acquired during a patient´s evolution, due to the selection of bacterial microbiota associated with antibiotic pressure or other methods such as transmission by healthcare personnel or as a result of recurrent infection. More recently, Álvarez-Paredes et al, 30 also have questioned the suitability of the CLSI criterion. They found differences between the resistance rates of isolates when comparing data obtained applying different criteria for duplicate isolate removal.…”
Section: Discussionmentioning
confidence: 99%